Penerapan Metode Bamboo Dancing Untuk Meningkatkan Hasil Pemahaman Teks Materi Qiro’ah Mahasiswa - Muhammad Syaifullah; Nailul Izzah; Hernisawati Hernisawati (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2020)
The purpose of Qiro'ah (reading) lessons is to train students to be able to understand texts individually. The application of an exciting and enjoyable learning strategy by a Lecturer that involves students actively in the process of understanding the reading content, either independently or in groups. Current learning models such as contextual learning and cooperative learning can also be adapted for learning to read. Improving students' Qiro'ah (reading) mastery results is a general objective of this study with a cooperative dancing type approach. The specific objectives of this study are (1) Describe the Qiro'ah learning process (reading) use of the bamboo dancing method of PBA students at IAIM NU Metro, and (2) Describe the results of increasing mastery of Qiro'ah learning (reading) of PBA students ) use of the bamboo dancing method. The design uses PTK with John Elliot Models. PBA third semester students are the subjects in this study. Information about the activities of lecturers and students and the results of the initial and final test scores in each cycle is the data in this study. Test questions, observation sheets, and interview guidelines are the instruments used in this study. Using steps is collecting data, reducing data, presenting data, and concluding research results. Whereas Planning, implementing, observing, and reflecting are the stages in this research. The results of the application of Qiro'ah learning using the bamboo dancing method in this study are the increased mastery of understanding in reading texts that is significant from each cycle and the initial tests before the action. The average grade on the initial test before action is 67 increased in cycle 1 79 as well as increasing again in cycle 2 91. So, it can be concluded that there is an increase in the understanding of students' Qiro'ah texts in each cycle.